2019
DOI: 10.1021/acsnano.9b06998
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Facets of the Periodic Table of Elements

Abstract: The 150th anniversary of the periodic table of elements highlights its tremendous role in chemistry, physics, biology, astronomy, philosophy, and engineering as a shining scientific breakthrough, shedding light on the fundamental laws of nature. Nanoscience and nanotechnology are multidisciplinary, focusing on nanoscale materials and processes, in which a variety of elements are used and single atoms are often manipulated. In this Perspective, we present a new viewpoint on what the renown periodic table can of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 81 publications
1
16
0
1
Order By: Relevance
“…Organic NMs, such as liposomes, dendrimers, micelles, or polymers are mainly composed of molecular carbon, hydrogen, oxygen, nitrogen, sulfur, and phosphorus. Inorganic NMs, those with particular intrinsic optical, magnetic, electronic, mechanical, or thermal properties are a broad group of materials consisting of specific s, p, d, and f-block elements to form single- or multi-element NMs [ 21 ]. Thus, these NMs may contain alkali metals (Li, K, and Cs), alkaline earth metals (Mg, Ca, Sr, and Ba), transition metals (Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Mo, Tc, Ru, Ph, Pd, Ag, W, Ir, Pt, and Au), post-transition metals (Al, Zn, Cd, In, Sn, Hg, Pb, and Bi), metalloids (Si, As, Sb, and Te), non-metals (H, C, N, O, P, S, and Se), lanthanides (La, Ce, Pr, Nd, Sm, Eu, Gd, and Yb), or an actinide (Ac) [ 21 , 22 ].…”
Section: Overview: Green Biosynthesis Of Metallic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic NMs, such as liposomes, dendrimers, micelles, or polymers are mainly composed of molecular carbon, hydrogen, oxygen, nitrogen, sulfur, and phosphorus. Inorganic NMs, those with particular intrinsic optical, magnetic, electronic, mechanical, or thermal properties are a broad group of materials consisting of specific s, p, d, and f-block elements to form single- or multi-element NMs [ 21 ]. Thus, these NMs may contain alkali metals (Li, K, and Cs), alkaline earth metals (Mg, Ca, Sr, and Ba), transition metals (Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Mo, Tc, Ru, Ph, Pd, Ag, W, Ir, Pt, and Au), post-transition metals (Al, Zn, Cd, In, Sn, Hg, Pb, and Bi), metalloids (Si, As, Sb, and Te), non-metals (H, C, N, O, P, S, and Se), lanthanides (La, Ce, Pr, Nd, Sm, Eu, Gd, and Yb), or an actinide (Ac) [ 21 , 22 ].…”
Section: Overview: Green Biosynthesis Of Metallic Nanoparticlesmentioning
confidence: 99%
“…Inorganic NMs, those with particular intrinsic optical, magnetic, electronic, mechanical, or thermal properties are a broad group of materials consisting of specific s, p, d, and f-block elements to form single- or multi-element NMs [ 21 ]. Thus, these NMs may contain alkali metals (Li, K, and Cs), alkaline earth metals (Mg, Ca, Sr, and Ba), transition metals (Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Mo, Tc, Ru, Ph, Pd, Ag, W, Ir, Pt, and Au), post-transition metals (Al, Zn, Cd, In, Sn, Hg, Pb, and Bi), metalloids (Si, As, Sb, and Te), non-metals (H, C, N, O, P, S, and Se), lanthanides (La, Ce, Pr, Nd, Sm, Eu, Gd, and Yb), or an actinide (Ac) [ 21 , 22 ]. Finally, the hybrid NMs can be sectioned as organic-on-inorganic, i.e., organic matter used to modify inorganic NMs, or vice versa, inorganic-in-organic, using inorganic constituents to modify organic materials.…”
Section: Overview: Green Biosynthesis Of Metallic Nanoparticlesmentioning
confidence: 99%
“…After millennia in which products were made using a small bunch of elements, in the past decades modern technology is using almost every element in the Periodic Table, but often only once. A recent editorial points out the nanotechnology facets of the Periodic Table exploiting elemental combinations to produce new advanced nanomaterials (Goodilin et al, 2019). It is interesting to note that presently Hi-Tech devices are manifactured with the best possible technologies we can devise, but are generally recycled using relatively basic approaches.…”
Section: The Periodic Table In the Circular Economy Eramentioning
confidence: 99%
“…It has been observed that facecentered cubic(FCC), hexagonal closed packing (HCP) and body-centered cubic(BCC) collectively contributed to 68% of stable lattice structures and hexagonal, rhombohedral (RHO), orthorhombic (ORTH), simple cubic(SC), monoclinic (MON), double hexagonal closed packed (DHCP) and tetragonal(TET) accounted for the rest. 37 The critical size plays a decisive role in the stability of crystal structure. The stability of FCC and BCC nanocrystals is decided if the size is smaller and larger than the critical size respectively.…”
Section: Introductionmentioning
confidence: 99%